2003
DOI: 10.1079/bjn2003966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tartaric acid and dietary fibre from sun-dried raisins on colonic function and on bile acid and volatile fatty acid excretion in healthy adults

Abstract: Sun-dried raisins are a source of dietary fibre and tartaric acid. The effects of tartaric acid on colon function have not been the focus of extensive research. The purpose of the present study was to evaluate the effects of dietary fibre and tartaric acid from sun-dried raisins on colon function and on faecal bile acid and short-chain fatty acid (SCFA) excretion in healthy adults. Thirteen healthy subjects were fed 120 g sun-dried raisins/d or 5 g cream of tartar (equivalent to the tartaric acid in 120 g sun-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 15 publications
(22 reference statements)
0
39
0
1
Order By: Relevance
“…The US Food and Drug Administration considers it a generally recognized as safe (GRAS) human food ingredient (3 ). Gram quantities of tartaric acid are commonly consumed in grapes and grape products, and many prepared foods contain large quantities of the acid or its salts (4,5 ). Dietary intake of tartaric acid by the two individuals in the study by Shaw et al (1 ) was not evaluated.…”
Section: Significance Of Urinary Tartaric Acidmentioning
confidence: 99%
“…The US Food and Drug Administration considers it a generally recognized as safe (GRAS) human food ingredient (3 ). Gram quantities of tartaric acid are commonly consumed in grapes and grape products, and many prepared foods contain large quantities of the acid or its salts (4,5 ). Dietary intake of tartaric acid by the two individuals in the study by Shaw et al (1 ) was not evaluated.…”
Section: Significance Of Urinary Tartaric Acidmentioning
confidence: 99%
“…We previously showed that the combination of dietary fiber and tartaric acid has beneficial effects on intestinal transit time (TT), fecal weight (FW), and fecal bile acid (FBA) composition. 1,2 Grapes and raisins are the only common foods that contain reasonable levels of tartaric acid in temperate climates, tamarind being the other fruit in tropical regions. Tamarind is used in some countries to help normalize bowel function.…”
mentioning
confidence: 99%
“…8 Dietary fiber has been shown to decrease the concentration of bile acids in the feces. 1,2,9 The purpose of this study was to determine the effect of SDR on colon function and health by measuring the response to increasing doses of raisins per day after a period free of consumption of raisins and other dried fruits. The key measurements were fecal weight, intestinal TT, and FBA.…”
mentioning
confidence: 99%
“…This hypolipidaemic effect of raisins might be due to polyphenols content interference with cholesterol absorption [60] and decrease of hepatic cholesterol concentrations as observed in guinea pigs [61] after diet supplementation with lyophilised grape powder. Similarly, the hypocholesterolaemic effects of raisins were proven by Spiller et al [51]. In addition, Bruce et al [11] and Gardner et al [24] reported that daily consumption of raisins improved lipid profile and increased plasma antioxidant capacity.…”
Section: Discussionmentioning
confidence: 85%
“…Animals were split randomly into four equal groups (n = 10). Group I served as control and received only saline through a nasogastric tube; group II represented the positive control and received 0.5 g of raisin homogenate through a nasogastric tube daily for 13 weeks, according to Spiller et al [51], after adjusting the human dose for a rat according to Paget and Barnes [40]; group III was the induction group where animals were fed a HCD, consisting of 95% rat chow supplemented with 4% cholesterol and 1% cholic acid, according to Thiruchenduran et al [54], for 13 weeks; and group IV represented the treated group, where the rats were fed a HCD along with raisin homogenate at the same dose. Food and water consumption, and body weight were measured at the start of the experiment, after 6 weeks, and by the end of the experiment.…”
Section: Animalsmentioning
confidence: 99%